Valorization of calcium phosphite waste as phosphorus fertilizer: Effects on green manure productivity and soil properties. (1st May 2021) - Fontana, Mario; Bragazza, Luca; Guillaume, Thomas; Santonja, Mathieu; Buttler, Alexandre; Elfouki, Saïd; Sinaj, Sokrat
Abstract: The potential to use calcium phosphite ( Ca-Phi ) as phosphorus (P) fertilizer may represent an effective recycling of P-containing by-products. A greenhouse experiment was conducted to investigate the effect of Ca-Phi (38 kg P ha −1 ) on soil properties and the growth parameters of four green manure species in clay and sandy soils using Ca-Phi, TSP (triple superphosphate) and control (no fertilization) as treatments. Eight weeks after sowing, we measured aboveground biomass yield, phosphite (Phi) concentration in plant biomass, different soil P pools as well as microbial biomass nutrients. Compared to control, the addition of Ca-Phi did not negatively affect green manure yield, except for lupine ( Lupinus albus L.) in clay soil. The Phi concentration in plant biomass varied across species and soil type with a maximum concentration of about 400 mg Phi kg −1 for mustard ( Brassica juncea L.) in clay soil. Compared to control, TSP and Ca-Phi fertilization had a similar effect on different P pools and microbial biomass nutrients (C, N and P) although the response was soil–type dependent. In the sandy soil, after Ca-Phi addition the amount of available P (PNHCO3 ) increased to the same extent as in the TSP treatment (i.e. around 6 mg P kg −1 ) suggesting that Ca-Phi was, at least partly, oxidized. In the clay soil with high P fixing capacity, Ca-Phi promoted higher PNaHCO3 than TSP likely due to different solubility of chemical P forms. Additional studies are however required to better understand soil microbial responses and to quantify the P agronomical efficiency for the following crop under Ca-Phi fertilization. Highlights: Phosphite accumulation in green manures varied depending on plant species and soil type. Calcium phosphite did not reduce the productivity of green manures. Calcium phosphite affected microbial biomass similarly to triple superphosphate fertilizer. Soil phosphate increased after calcium phosphite addition due to phosphite oxidation.